Gamma‐Ray Irradiation Assisted Polyacrylamide Gel Synthesis of Scheelite Type BaWO4 Phosphors and Its Colorimetric, Optical and Photoluminescence Properties. Issue 34 (10th September 2020) - Tang, Shengnan; Wang, Shifa; Yu, Xianlun; Gao, Huajing; Niu, Xiaowei; Wang, Yong; Zhao, Xinxin; Sun, Guangzhuang; Li, Dengfeng
Abstract: A gamma‐ray irradiation assisted polyacrylamide gel method is used to synthesize the scheelite‐type barium tungstate (BaWO4 ) phosphors with space group I41/a(88). Various instruments were employed to characterize and reveal the phase purity, microcosmic characteristics, chemical composition, surface micromorphology, colorimetric, optical and photoluminescence properties of BaWO4 phosphors. The phase structure and functional group analysis showed that the formation temperature of pure BaWO4 phosphor was 100 °C lower than calcium tungstate (CaWO4 ) and strontium tungstate (SrWO4 ). The characterization of particle growth showed that BaWO4 was easy to grow along (112) and (200) crystal planes. The optical band gap (Eg) value of BaWO4 first increases and then decreases with the increasing of sintering temperature. The sintering temperature causes the BaWO4 xerogel to produce a variety of colors from black to white. The photoluminescence spectra showed that two obvious emission peaks at 380 and 415 nm are observed when the excitation wavelength is 334 nm. The former is ascribed to the T1(2) →A1(1) transition and the latter could be attributed to the defect energy levels in the BaWO4 phosphors. The intensity of emission peak at 380 nm decreases with the increasing sintering temperature. The photoluminescence mechanism of scheelite‐type BaWO4 phosphor was explored on the basis of energy band theory and experimental results. Abstract : A gamma‐ray irradiation assisted polyacrylamide gel method has been used to synthesize the scheelite‐type barium tungstate (BaWO4 ) phosphors. The average particle size of BaWO4 phosphor is about 60 nm. The scheelite‐type barium tungstate (BaWO4 ) phosphors exhibits two obvious emission peaks at 380 and 415 nm with the excitation wavelength is 334 nm.